2013
DOI: 10.1523/jneurosci.3175-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Stress Switches Cannabinoid Type-1 (CB1) Receptor-Dependent Plasticity from LTD to LTP in the Bed Nucleus of the Stria Terminalis

Abstract: The bed nucleus of the stria terminalis (BNST) exerts a coordinated modulation of the psychoneuroendocrine responses to stress. However, how acute stress impacts on BNST in vivo plasticity is a crucial question that still remains unanswered. Here, neurons from the anterior portion of the BNST (aBNST) were recorded in vivo during and after stimulation of their medial prefrontal cortical (mPFC) afferents. In C57BL/6N mice, a 1 h restraint stress induced a switch from long-term depression (LTD) to long-term poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 25 publications
3
40
0
Order By: Relevance
“…Specifically, studies examining the effects of CB1 stimulation in the BNST have shown that exposure to stress causes a switch in the effects on CB1 receptor stimulation on neuronal firing. Rather than promoting LTD, CB1 receptor activation after stress promotes LTP (Glangetas et al, 2013). Consistent with this switch in functionality, it has also been reported that the application of a CB1 receptor agonist to hippocampal slices from stressed animals switches CB1 receptor activation from suppressing glutamatergic transmission to enhancing LTP (Reich et al, 2013).…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effementioning
confidence: 55%
“…Specifically, studies examining the effects of CB1 stimulation in the BNST have shown that exposure to stress causes a switch in the effects on CB1 receptor stimulation on neuronal firing. Rather than promoting LTD, CB1 receptor activation after stress promotes LTP (Glangetas et al, 2013). Consistent with this switch in functionality, it has also been reported that the application of a CB1 receptor agonist to hippocampal slices from stressed animals switches CB1 receptor activation from suppressing glutamatergic transmission to enhancing LTP (Reich et al, 2013).…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effementioning
confidence: 55%
“…If alterations in BNST structure, function, or connectivity indeed underlie these disorders in humans, then the BNST becomes a novel, untapped treatment target. Supporting this potentially novel role is evidence from rodent studies that anxiety and addiction processes may be altered by drugs that target the BNST, including CRF antagonists (Walker et al, 2009), norepinephrine agonists (Park et al, 2013;Harris and Gewirtz, 2004) and antagonists (Wenzel et al, 2014), and endocannabinoid system targets (Glangetas et al, 2013).…”
Section: The Human Bnstmentioning
confidence: 99%
“…Stress is known to cause a long-lasting increase in anxiety-like behavior, and as the BNST is a crucial structure in modulating both the stress response and anxiety behavior, it is reasonable to predict that stress would cause a long-lasting change in BNST synaptic plasticity. In fact, multiple studies have shown that stress can affect synaptic plasticity in the BNST (Conrad et al, 2011;Dabrowska et al, 2013b;Francesconi et al, 2009;Glangetas et al, 2013;McElligott and Winder, 2007), however the results of these studies are seemingly inconsistent. In this section, we will re-examine these studies in light of how stress interacts with neuromodulators as discussed above and new research on the distinct roles of different BNST sub-nuclei in modulating anxiety-like behavior.…”
Section: Stress Modulation Of Synaptic Plasticitymentioning
confidence: 99%
“…Acute stress can cause a 10 Hz stimulation of the medial prefrontal cortex (mPFC) input into the BNST to switch from resulting in a long-term depression (LTD) to a long-term potentiation (LTP). The functional consequence of this switch from LTD to LTP is unknown; perhaps it acts to boost the signal of salient events after acute stress (Glangetas et al, 2013). The BNST serves as a relay between the mPFC and VTA DA neurons.…”
Section: Stress Modulation Of Synaptic Plasticitymentioning
confidence: 99%